Treating cutaneous squamous cell carcinoma using 5-aminolevulinic acid polylactic-co-glycolic acid nanoparticle-mediated photodynamic therapy in a mouse model - Wang X (Dove Medical Press, 2015)
Xiaojie Wang,1,2,* Lei Shi,2,* Qingfeng Tu,2 Hongwei Wang,3 Haiyan Zhang,2 Peiru Wang,2 Linglin Zhang,2 Zheng Huang,4 Feng Zhao,5 Hansen Luan,5 Xiuli Wang2 1Shanghai Skin Diseases Clinical College of Anhui Medical University, 2Shanghai Skin Disease Hospital, 3Huadong Hospital, Fudan University, Shanghai, 4MOE Key Laboratory of OptoElectronic Science and Technology for Medicine, Fujian Normal University, Fuzhou, 5National Pharmaceutical Engineering Research Center, China State Institute of Pharmaceutical Industry, Shanghai, People’s Republic of China *These authors contributed equally to this study Background: Squamous cell carcinoma (SCC) is a common skin cancer, and its treatment is still difficult. The aim of this study was to evaluate the effectiveness of nanoparticle (NP)-assisted 5-aminolevulinic acid (ALA) delivery for topical photodynamic therapy (PDT) of cutaneous SCC.Materials and methods: Ultraviolet-induced cutaneous SCCs were established in hairless mice. ALA-loaded polylactic-co-glycolic acid (PLGA) NPs were prepared and characterized. The kinetics of ALA PLGA NP-induced protoporphyrin IX fluorescence in SCCs, therapeutic efficacy of ALA NP-mediated PDT, and immune responses were examined.Results: PLGA NPs enhanced protoporphyrin IX production in SCC. ALA PLGA NP-mediated topical PDT was more effective than free ALA of the same concentration in treating cutaneous SCC.Conclusion: PLGA NPs provide a promising strategy for delivering ALA in topical PDT of cutaneous SCC. Keywords: 5-aminolevulinic acid (ALA), polylactic-co-glycolic acid (PLGA), nanoparticles (NPs), cutaneous squamous cell carcinoma (SCC), photodynamic therapy (PDT), microneedling